Ceramiche fini dai contesti tardi dell’Edificio Sud a Gortina: produzione locale e importazioni dall’Africa - Giuliodori, Marzia (Rei Cretariae Romanae Fautorum Acta, 2022)
The later contexts of the Byzantine house quartier at Gortyna (Crete), particularly those of the South Building and West Road, dated between the middle/end of the 7th and the beginning of the 8th centuries AD, have produced large amounts of fine tableware sherds. The numerous fragments of fine Byzantine painted pottery, pertaining to open and closed shapes, were locally produced. At the same time, African Red Slip ware sherds, the latest of the pottery classes recovered through the excavation, were also found. This paper takes into consideration this class of materials, especially D3 and D4 productions, whose clay fabric seems to be related to the so-called ‘Egyptian Red Slip Ware C’ as defined by Hayes. This kind of fabric also characterized the pottery from the Praetorium (D4 production). Thus, this ‘Egyptian Red Slip Ware C’ is to be identified with the late production of the Tunisian workshops, circulating in the Mediterranean between the end of the 7th and the first decades of the 8th centuries AD. This sheds further light on the trade links between Crete and Africa Proconsularis in a late period.